2005
DOI: 10.1128/jvi.79.3.1871-1887.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of RNA Templates and Encapsidation of Spliced Viral RNA Are Influenced by the Arginine-Rich Domain of Human Hepatitis B Virus Core Antigen (HBcAg 165-173)

Abstract: Previously, human hepatitis B virus (HBV) mutant 164, which has a truncation at the C terminus of the HBV core antigen (HBcAg), was speculated to secrete immature genomes. For this study, we further characterized mutant 164 by different approaches. In addition to the 3.5-kb pregenomic RNA (pgRNA), the mutant preferentially encapsidated the 2.2-kb or shorter species of spliced RNA, which can be reverse transcribed into double-stranded DNA before virion secretion. We observed that mutant 164 produced less 2.2-kb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(187 citation statements)
references
References 63 publications
7
179
0
1
Order By: Relevance
“…This phenotype is reminiscent of HBV core protein mutants bearing mutations within the arginine-rich carboxy terminus, which also contains three serine phosphorylation sites. 41,42 Therefore, it will be interesting to determine whether anti-hepadnaviral A3G activity may be mediated and/or modulated by HBV core protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is reminiscent of HBV core protein mutants bearing mutations within the arginine-rich carboxy terminus, which also contains three serine phosphorylation sites. 41,42 Therefore, it will be interesting to determine whether anti-hepadnaviral A3G activity may be mediated and/or modulated by HBV core protein phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon nucleation around the RNA, the capsomers aggregate to form viruses of various T-number sizes with N segments inside and N 0 − N segments outside. It has been suggested that the outside fragments can be removed by nucleases (17,18). We focus on the subpopulation of singly encapsidated viral particles of a particular T-number.…”
Section: Clarification Of the Optimal Genome Lengthmentioning
confidence: 99%
“…The three-dimensional map reveals a protein architecture highly similar to that of HBcAg-149 [5][6][7]. The inner space of the HBcAg-154 particle is also nearly empty, indicating the minimum volume of RNA inside [10]. This is an outcome because its short C-terminal tail lacks enough arginines to package RNA.…”
Section: The Inner Structure Of Hbcag-154mentioning
confidence: 84%
“…As one kind of HBcAg particle constructed by the entire core protein, HBcAg-183 encapsidates large amounts of RNA in the capsid. In addition, HBcAg particles truncated between residues 154 and 183, such as HBcAg-164, 169, 171 and 173, also contain obvious RNA densities inside for their basic C-terminal tails which are longer than that of HBcAg-154 [10].…”
Section: The Inner Structure Of Hbcag-154mentioning
confidence: 99%
See 1 more Smart Citation